Material EasyGraft: bone regeneration in the experiment and clinical effectiveness of osteoplasty in patients with generalized periodontitis - Dmitrieva E.O. (Морфологія, 2015)
ABSTRACT. Background. The theoretical basis of osteoplasty, fully supported by clinical observations, is that violations occur in periodontitis of correlation between tooth and the surrounding tissues, including the microcirculation. Objective. The aim was experimental evaluation of tissue alterations in bone implant material Easy-Graft®, as well as determining the dynamics of clinical and instrumental parameters after its use in the surgical treatment of patients with generalized periodontitis I-III degree for 1 year. Methods. The analysis of quantitative morphological estimation of regenerative processes in osteal tissue in model of osteal defect is carried out at implantation of material Easy-Graft® at this work. It was investigated dynamics of clinical and instrumental parameters after its use in the surgical treatment of patients with generalized periodontitis I-III degree during 1 year. Results. We found out that Easy-Graft® undergo resorbtion and thus optimize bone regeneration. Regeneration is accompanied by decreased specific area of the particles implanted and increased integration index and specific density of trabeculae within the reaction zone. Highest intensity of these processes was ob-served in the period from 15th fill the 30th day after implantation. In patients with chronic generalized periodontitis use of Easy-Graft® improves most periodontal indices, limits the extent of pathological tooth mobility and gingival recession index, increases capillary resistance, prevents the growth of vertical alveolar ridge resorption. Conclusion. The most significant clinical efficiency of osteoplasty with Easy-Graft® observed in mature and elderly patients, regardless of the sex of the patients.